(untitled) (Universal International Scientific Journal, 2026)
This article is dedicated to highlighting the importance of early detection and timely treatment of congenital visual disorders in children, as well as explaining, on a scientific basis, the negative consequences that may arise if no interventions are undertaken. Congenital visual disorders directly affect the development of the visual system in children, disrupting the normal maturation of the visual analyzer. In particular, if these pathologies are not identified or adequately treated during the early years of life, profound and irreversible functional changes may occur in the visual system. Research indicates that congenital visual disorders can lead to the development of amblyopia (lazy eye), impaired binocular vision, decreased visual acuity, and strabismus. Furthermore, insufficient visual stimulation may result in inadequate formation of neural connections in the visual areas of the cerebral cortex or irreversible neuronal changes. This not only limits visual function but also negatively impacts the child’s cognitive development, academic performance, and social adaptation. According to scientific sources, early diagnosis and treatment during the neuroplastic period of the visual system, id est, in the initial stages of childhood, are highly effective and can significantly improve visual functions. Therefore, widespread implementation of visual screening in children, early identification of congenital visual disorders, and development of individualized treatment strategies for each child are considered among the top priorities in pediatric ophthalmology